2015
DOI: 10.2310/7750.2014.13192
|View full text |Cite
|
Sign up to set email alerts
|

A Clinicopathologic Review of a Case Series of Dermatofibrosarcoma Protuberans with Fibrosarcomatous Differentiation

Abstract: DFSP-FS represents a more aggressive subtype of DFSP. Several features of DFSP-FS may impart a higher risk of metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 23 publications
0
8
0
1
Order By: Relevance
“…Fine-needle aspiration cytology has low diagnostic accuracy for mesenchymal breast tumor. Core biopsy is considered the optimal procedure for diagnosing such tumors, though adjunctive immunohistochemical analysis is often required (1821). However, a diagnosis from a core biopsy is often difficult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fine-needle aspiration cytology has low diagnostic accuracy for mesenchymal breast tumor. Core biopsy is considered the optimal procedure for diagnosing such tumors, though adjunctive immunohistochemical analysis is often required (1821). However, a diagnosis from a core biopsy is often difficult.…”
Section: Discussionmentioning
confidence: 99%
“…It was concluded that primary or recurrent treatment of DFSP should be excision with negative margins, which should result in low recurrence rates and infrequent metastatic spread. Multimodality treatment, particularly the use of tyrosine kinase inhibitors, could be effective, but should not be considered as curative (5,18,21,2429). DFSP follow-ups subsequent to surgery are recommended for a minimum of 3 years, in 6-month intervals (18).…”
Section: Discussionmentioning
confidence: 99%
“…Fibrosarcomatous components are indistinguishable from a highgrade fibrosarcoma. This can be compared to the uniform, low-grade DFSP characterized by a storiform or cartwheel pattern [13]. The myxoid changes seen in our patient are rare in classic DFSP but seem to be more commonly found in FS-DFSP [4].…”
Section: Discussionmentioning
confidence: 52%
“…These tumors may be local or found invading local tissues, including subcutaneous tissue and skeletal muscle. While FS-DFSPs show considerable variability in presentation, consistently they demonstrate an association with higher rate of metastasis (10-15% vs. less than 1%) and poorer prognosis compared to low-grade DFSP [4,5,13,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation